Evidence for Infection and Inflammation in Infant Deaths in a Country with Historically Low Incidences of Sudden Infant Death Syndrome - Törő, Klára; Vörös, Krisztina; Mészner, Zsófia; Váradi-T, Aletta; Tóth, Adrienn; Kovács, Katalin (Frontiers in Immunology, 2015)
Total infant mortality in Hungary has been higher than other European countries; however, the reported incidence of Sudden Infant Death Syndrome (SIDS) has been lower than those of Western Europe and the United States. The low incidence of SIDS in Hungary has been supported by evidence obtained from the high rate of scene of death investigation and medico-legal autopsy mandatory since the 1950s. In this study, we compared the incidence of explained and unexplained infant deaths in Hungary for three periods: 1979-1989 when the incidence of SIDS was high in western Europe; 1990-1999 when the incidence of infant deaths was falling following introduction of the public health campaigns to reduce the risk factors associated with SIDS; 2000-2012 to determine if introduction of Hib or pneumococcal vaccines or introduction of an earlier immunization schedule during this period had an effect on SIDS or SUDI. Explained infant deaths fell consistently during this period; however, unexplained deaths (SIDS) rose during the second period when the incidence of SIDS was falling in other European countries. Evidence for infection and/or inflammation was observed for the majority of SIDS during each period. The results are discussed in relation to campaigns to reduce infant mortality in Hungary and the introduction of new vaccines and an earlier immunization schedule in 2006.